Direct and Indirect Effects on Earnings of Schooling and Socio-Economic Background - Morgenstern, Richard D. (The Review of Economics and Statistics, 1973)
T HE effects of schooling (as measured both by years attained and by one or more dimensions of quality), and socio-economic background in determining individuals' earnings, have long been controversial issues. In the past decade, with the advent of large scale empirical studies, a number of widely held but not well documented hypotheses about these issues have failed to find broad support in the data. Namely (a) several recent studies, most notably that by Coleman and his associates (1966), have found only a most tenuous relationship between conventional measures of the quality of school inputs and various achievement test scores and (b) the notion that socio-economic background is important in determining an individual's income has been played down in the literature concurrent with the rise in popularity of the human capital explanation of earnings differences (for example, Mincer (1970)). The purpose of this paper is to re-examine the relationship among income, socio-economic background, years of schooling and quality of school inputs. Several models are postulated which permit the examination of both the direct and the indirect effects of the various factors, separately for blacks and for whites. The primary data source is the 1968 Urban Problems Survey conducted by the Survey Research Center. The principal conclusions of this paper are: (a) school quality has a small direct effect on the wage rates of blacks but no apparent effect at all on the wages of whites; (b) for both races school quality has strong indirect effects as it influences the number of years of schooling attained; (c) socio-economic background, as variously measured, appears to have significant direct effects on earnings and, like school quality, indirect effects as it also influences the number of years of education attained; and (d) years of schooling appears to exert a strong influence on earnings independent of other measured variables, especially for whites.